Penerapan Strategi Pemasaran Dalam Menarik Minat Konsumen pada UMKM : (Studi Kasus Kedai Siempur) - Dwi Yanti Wahyu Lestari; Tazkia Nehayata Muna; Lilis Renfiana (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Marketing strategy is a tool to achieve success in attracting consumer buying interest without destroying relationships with entrepreneurs who produce the same goods. Usually, marketing strategy is said to be the basis for preparing an overall business plan. This research aims to gain knowledge about marketing strategies in attracting consumer interest, as well as an overview of how effective the implementation of marketing strategies is. The research was conducted at Kedai Siempur. The research uses descriptive qualitative research with observation and interview data collection techniques. From the results of the analysis of the implementation of marketing strategies at Kedai Siempur, they have implemented a segmentation strategy in which there is no consumer specialization, in terms of targeting they have provided maximum service and listened to input from consumers, and in positioning they prioritize quality ingredients and hold promotions so that consumers are interested. , and has implemented a marketing mix including product, price, location and promotion. This shows an increase in total sales from month to month and this is used as a reference in maintaining a marketing strategy to attract consumer buying interest in Kedai Siempur.